2015
DOI: 10.1371/journal.pone.0128959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Electrical Stimulation on the Masticatory Muscles and Physiologic Sleep Variables in Adults with Cerebral Palsy: A Novel Therapeutic Approach

Abstract: Cerebral palsy (CP) is a term employed to define a group of non-progressive neuromotor disorders caused by damage to the immature or developing brain, with consequent limitations regarding movement and posture. CP may impair orapharygeal muscle tone, leading to a compromised chewing function and to sleep disorders (such as obstructive sleep apnea). Thirteen adults with CP underwent bilateral masseter and temporalis neuromuscular electrical stimulation (NMES) therapy. The effects on the masticatory muscles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The intrinsic factors include immune response deficiency, a high amount of periopathogens, sleep disorders such as obstructive sleep apnea, dysfunction of the oropharyngeal muscles resulting in severe dysphagia, and the risk of occurrence for aspiration pneumonia. Previous studies confirm the presence of respiratory pathogens in the oral cavity which may be aspirated into the lung alveoli due to severe dysphagia, developing aspiration pneumonia [12,13]. This comorbidity may negatively influence the oral health homeostasis, aggravating the preexistent inflammatory processes, in particular, the PD.…”
Section: Special Health Care Needs (Shcn) In Dentistrymentioning
confidence: 89%
See 1 more Smart Citation
“…The intrinsic factors include immune response deficiency, a high amount of periopathogens, sleep disorders such as obstructive sleep apnea, dysfunction of the oropharyngeal muscles resulting in severe dysphagia, and the risk of occurrence for aspiration pneumonia. Previous studies confirm the presence of respiratory pathogens in the oral cavity which may be aspirated into the lung alveoli due to severe dysphagia, developing aspiration pneumonia [12,13]. This comorbidity may negatively influence the oral health homeostasis, aggravating the preexistent inflammatory processes, in particular, the PD.…”
Section: Special Health Care Needs (Shcn) In Dentistrymentioning
confidence: 89%
“…This biostimulating effect also reflected in the electrical activity of the oropharyngeal muscles, favoring their functional performance; then, a positive effect on the apnea and hypopnea index was found. These episode cascades reduced the number of pathological respiratory events, promoting improvements in the quality of life for these patients [12][13][14].…”
Section: Special Health Care Needs (Shcn) In Dentistrymentioning
confidence: 99%
“…Power analysis or Power test is the process used for determining the sample size for this study, using SPSS (version 22.0.0.0). This is based on a work entitled “Effects of Neuromuscular Electrical Stimulation on the Masticatory Muscles and Physiologic Sleep Variables in Adults with Cerebral Palsy: A Novel Therapeutic Approach” [15]. The intervention was considered to result in a minimum effect similar to the EMG activity of the masseter and temporalis muscles in disabled adults.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, previous studies have suggested that new therapeutic approaches are promising options to improve masticatory muscle function and to treat sleep disorders, including sleep bruxism and OSA. These investigations have demonstrated satisfactory results in patients with disabilities who presented concomitant unbalanced masseter and temporalis muscle patterns, sleep bruxism, and OSA [1315].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum bite force may be measured through electromyography, considering this technique is an important tool in the assessment of mandibular movements and neuromuscular performance during chewing. [15]…”
Section: Introductionmentioning
confidence: 99%